MANAJEMEN STRATEGI PEMASARAN PENDIDIKAN DALAM MENINGKATKAN DAYA SAING LEMBAGA PENDIDIKAN DI MADRASAH ALIYAH SWASTA LABORATORIUM KOTA JAMBI - Zhainatun Sofiroh; Fridiyanto; Boby Yasman Purnama (STKIP Subang, 2026)
This study is motivated by the increasing competition among educational institutions, particularly private schools, which requires effective marketing strategy management to maintain institutional existence and enhance competitiveness. MAS Laboratorium Jambi City, as an Islamic educational institution, possesses unique potential through its laboratory- and research-based learning approach; however, it faces challenges in transforming this potential into a competitive and persuasive marketing strategy. This study aims to describe and analyze the implementation of educational marketing strategy management and to examine its impact on the institution’s competitiveness. The research employs a qualitative descriptive approach, with data collected through observation, interviews, and documentation involving the principal, teachers, and related stakeholders. The findings reveal that MAS Laboratorium Jambi City has successfully developed a positive public image through improvements in infrastructure and student achievements, which contributes to increased community interest despite relatively standard educational costs. However, the marketing strategies implemented are still partial and not yet fully integrated, particularly in terms of persuasive communication and consistent utilization of digital platforms. Therefore, strengthening integrated marketing strategies and optimizing digital engagement are essential to enhance the institution’s competitive advantage in a sustainable manner.